Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
3.2 - 9x + 7.1 - 3x
Combine like terms.
-9x - 3x = -12x
3.2 + 7.1 = 10.3
So we have:
-12x + 10.3
Combine like terms.
-9x - 3x = -12x
3.2 + 7.1 = 10.3
So we have:
-12x + 10.3
3.2 - 9x + 7.1 -3x
We need to combine like terms. Like terms are the values that have the same variable. So 9x and 3x are like terms, and 3.2 and 7.1 are also like terms.
So we can reorder the qeustion to:
3.2 + 7.1 -9x - 3x
Now we just simplify this, and it becomes:
10.3 - 9x - 3x
To simplify -9x -3x we can simply ignore the variable do the subtraction and bring back the variable:
-9x -3x = -9 - 3 = -12 = -12x
Another way to visualize it is if we take x as a factor, so:
-9x-3x = x(-9-3) = x(-12) = -12x
So anyways, our final answer will be:
3.2 - 9x + 7.1 - 3x = 10.3 - 12x
We need to combine like terms. Like terms are the values that have the same variable. So 9x and 3x are like terms, and 3.2 and 7.1 are also like terms.
So we can reorder the qeustion to:
3.2 + 7.1 -9x - 3x
Now we just simplify this, and it becomes:
10.3 - 9x - 3x
To simplify -9x -3x we can simply ignore the variable do the subtraction and bring back the variable:
-9x -3x = -9 - 3 = -12 = -12x
Another way to visualize it is if we take x as a factor, so:
-9x-3x = x(-9-3) = x(-12) = -12x
So anyways, our final answer will be:
3.2 - 9x + 7.1 - 3x = 10.3 - 12x
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.